Knowledge and practice of vaccination logistics management among primary health care workers in Nigeria - Wasiu Olalekan Adebimpe; Oluwatosin Adediran Adeoye (Taylor & Francis Group, 2021)
Vaccines are highly thermo-sensitive materials whose potency requires a functional cold chain system which is dependent on the ability of health care workers to effectively manage the system toward eliminating vaccine-preventable diseases. This study assessed knowledge and practice of vaccination logistic management systems among primary health care workers in Osun state Nigeria. It was a descriptive cross-sectional study among 180 randomly selected health care workers who took part in a larger study on the design and pretesting of vaccine cold chain (VACOC) coolers. Research instruments were self-administered semi-structured pretested questionnaire that was analyzed using the SPSS version 23.0. The mean age was 36.7 ± 8.9 years, 87 (48.3%) could correctly explain the vaccination logistic management system, 132 (73.3%) had been trained on the system, 129 (71.7%) could assemble the ice packs used in the vaccine career box, 135 (75.0%) could assemble the vaccines, while 145 (80.6%) could assemble the diluents and thermometer. One hundred and fifty-one (83.9%) and 146 (81.1%) were found to have good knowledge and attitude to the management systems, respectively. Spending more than 5 years in profession, being a male, being a Community Health Officer were significant predictors of having a good practice of immunization logistic management system. Some gaps in knowledge, attitude, and practice of vaccination cold chain logistic system still exist among studied respondents, and these should be addressed by stakeholders in immunization programs.